2018
DOI: 10.1038/s41388-018-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

The renin angiotensin system (RAS) mediates bifunctional growth regulation in melanoma and is a novel target for therapeutic intervention

Abstract: Despite emergence of new systemic therapies, metastatic melanoma remains a challenging and often fatal form of skin cancer. The renin-angiotensin system (RAS) is a major physiological regulatory pathway controlling saltwater equilibrium, intravascular volume and blood pressure. Biological effects of the RAS are mediated by the vasoactive hormone angiotensin II (AngII) via two receptor subtypes, AT1R (encoded by AGTR1) and AT2R (encoded by AGTR2). We report decreasing expression and increasing CpG island methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…CpG islands are regions of the genome, which are in close proximity to the promoter and regulate its activity; methylation of CpG islands leads to promoter inactivation. [69] However, even though this study provided a whole set of data, which consistently supported the authors' conclusions, the more common notion on the role of angiotensin receptors in cancer in the scientific literature is that the AT 1 R acts pro-proliferative, while the AT 2 R is a tumor suppressor that inhibits proliferation, migration and metastasis. [72,73] In fact, another very recent study by Martinez-Meza et al [71] reported that selective stimulation or overexpression of AT 2 Rs in mouse B16/F10 and human A375 melanoma cells reduced "normal" and transendothelial migration.…”
Section: Role Of Angiotensin Receptors In Melanoma Cell Proliferatisupporting
confidence: 80%
See 1 more Smart Citation
“…CpG islands are regions of the genome, which are in close proximity to the promoter and regulate its activity; methylation of CpG islands leads to promoter inactivation. [69] However, even though this study provided a whole set of data, which consistently supported the authors' conclusions, the more common notion on the role of angiotensin receptors in cancer in the scientific literature is that the AT 1 R acts pro-proliferative, while the AT 2 R is a tumor suppressor that inhibits proliferation, migration and metastasis. [72,73] In fact, another very recent study by Martinez-Meza et al [71] reported that selective stimulation or overexpression of AT 2 Rs in mouse B16/F10 and human A375 melanoma cells reduced "normal" and transendothelial migration.…”
Section: Role Of Angiotensin Receptors In Melanoma Cell Proliferatisupporting
confidence: 80%
“…The B16/ F10 mouse melanoma cell line is an exception and possesses only AT 2 Rs. [68][69][70][71] Normal melanocytes express exclusively AT 1 Rs. [2,69]…”
Section: Angiotensin Receptor Expression In Skin Cancermentioning
confidence: 99%
“…These medications are most commonly used for the treatment of hypertension, acute myocardial infarction, heart failure, and diabetic nephropathy. However, ACEIs and ARBs have also been considered as potential anti-tumor agents given the possible role of angiotensin II in melanoma progression (Renziehausen et al, 2019). Furthermore, both ACEIs and…”
Section: Ace Inhib Itor S and Ang I Oten S In Recep Tor B Lo Ck Er Smentioning
confidence: 99%
“…The AT 1 Ri sr esponsible for cell proliferation, angiogenesis, oxidative stress, and cardiovascular dysfunctions, whereas the AT 2 R has been reported to counteracts everal of the effectsm ediated by the AT 1 R, conferring cardio-protection, [2] antiproliferation,a ntiinflammation, and neuroregeneration. [3] Recently, we identified that AT 2 Rc an provide therapeutic opportunities in melanomas, [4] human pancreatic ductal adenocarcinoma, [5] and breast cancer. [6] In addition, we showed that AGTR 1 CpG island methylation in serum could serve as a novel biomarker of metastaticm elanoma.…”
mentioning
confidence: 99%
“…[6] In addition, we showed that AGTR 1 CpG island methylation in serum could serve as a novel biomarker of metastaticm elanoma. [4] These discoveries were feasible owing to the establishmento fo ur selectivec ompound, [Y] 6 -Angiotensin II, for the AT 2 R. [6] Witha ni ncreasing body of evidence indicating that selectivet argeting of AT 2 R can provide ab etter treatment for many different diseases, [7] there is an imminentn eed to further develop angiotensin receptor subtype-selective ligands.…”
mentioning
confidence: 99%